Comorbid personality difficulties are not associated with poorer outcomes for online cognitive behaviour therapy for symptoms of anxiety and depression. (2nd March 2021) - Mahoney, Alison E.J.; Haskelberg, Hila; Mason, Elizabeth; Millard, Michael; Newby, Jill
Abstract: Little is known about the prevalence and impact on treatment of comorbid personality disorders for adults undertaking online cognitive behaviour therapy (internet‐delivered or internet‐based cognitive behaviour therapy (iCBT)) for anxiety and depressive disorders. This study explored how common comorbid personality difficulties were in a large sample of consecutive patients ( N  = 1 132) seeking iCBT for their symptoms of anxiety and depression in routine care settings. Patients completed the Standardized Assessment of Personality‐abbreviated Scale Self‐Report prior to commencing an iCBT programme, as well as completing assessments of anxiety and depression symptom severity and psychological distress pre‐iCBT and post‐iCBT. Consistent with previous studies, a high proportion of the sample (62.6%) reported experiencing comorbid personality difficulties. However, comorbid personality difficulties were not significantly associated with poorer treatment adherence or higher post‐treatment symptom severity or psychological distress (controlling for baseline symptom severity, demographic characteristics and treatment variables). Current findings support an inclusive approach to iCBT provision where comorbid personality difficulties do not appear to be a contraindication for treatment. © 2021 John Wiley & Sons, Ltd.